2004
DOI: 10.1111/j.0959-9673.2004.00381.x
|View full text |Cite
|
Sign up to set email alerts
|

In situ analysis of lung antigen‐presenting cells during murine pulmonary infection with virulent Mycobacterium tuberculosis

Abstract: Scarce information exists about the role of lung antigen-presenting cells (APCs) in vivo during pulmonary tuberculosis. As APCs activate cellular immunity, following intratracheal inoculation with virulent Mycobacterium tuberculosis, we assessed in situ lung APC recruitment, distribution, granuloma involvement, morphology and mycobacterial burden by using MHC-CII, CD14, scavenger receptor class A (SRA), the murine dendritic cell (DC)-restricted marker CD11c and Ziehl-Neelsen staining. CD11c(+) DC and CD14(+) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…1). This is in agreement with the strong SR-A upregulation reported 3-9 wk after M. tuberculosis infection in mice (56), as well as in human pulmonary macrophages from tuberculosis patients (57). However, MARCO expression was not affected 1-4 wk after M. tuberculosis infection in our model (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 92%
“…1). This is in agreement with the strong SR-A upregulation reported 3-9 wk after M. tuberculosis infection in mice (56), as well as in human pulmonary macrophages from tuberculosis patients (57). However, MARCO expression was not affected 1-4 wk after M. tuberculosis infection in our model (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Our data showed that the percentage of CD11c ϩ DC in the lungs increased throughout infection, suggesting that there was DC infiltration into the lungs during infection. DC infiltration into the lungs has also been reported with other proinflammatory stimuli in the lung, including gamma interferon (27), cigarette smoking (73), and allergen inhalation (53,54), as well as during bacterial and viral infections (53,54,62). Also, the percentage of the lung DC that expressed the maturation marker CD80 significantly increased, and the levels of CD86 and MHC-II increased moderately throughout the course of the infection, suggesting that pulmonary cryptococcal infection leads to DC maturation.…”
Section: Fig 4 Effect Of Infection With C Neoformans On the Percenmentioning
confidence: 90%
“…By examining confocal images, we determined that the C. neoformans cells were indeed inside the DC. In studies of other pathogens that infect the lung, such as M. tuberculosis (28,62,64,66) and A. fumigatus (11), lung DC have been shown to phagocytose the organisms in vivo and are responsible for initiating an adaptive immune response. Moreover, we have shown previously that DC phagocytose C. neoformans in vitro when it is opsonized by complement or antibody (38).…”
Section: Fig 4 Effect Of Infection With C Neoformans On the Percenmentioning
confidence: 99%
See 1 more Smart Citation
“…13,89 Dendritic cells infected with Mtb have an impaired ability to present lipid antigens, possibly due to delay of maturation mediated by cell wall components, and are retained at the lung for prolonged periods compared to DCs that have taken up model antigens. 163 Interestingly, it has been shown in vitro that more virulent strains of Mtb, the Beijing strains in particular, inhibit the maturation of DCs and the ability of DCs to present lipid antigens through decreased expression of CD1. 192 The activated T cells specific for mycobacterial antigens migrate to the lungs to participate in granuloma formation.…”
Section: Cellular Responsementioning
confidence: 99%